Current Challenges and Approaches in Recommending Venues by Using Contextual Suggestion Track from TREC - Tan, KianLam; Ur Rehman Khan, Haseeb; Kim Lim, Chen (International Journal of Engineering and Technology, 2018)
Contextual suggestion systems have been emerging as an entrance region of research, attributable to the innovative advances in smart connecting things and rapid growth of Big Data. In this regard, the primary purpose of contextual suggestion systems is to propose things that assist users to settle on choices from countless activities, for example, according to their specific context, the system may predict what place users would find interesting to visit or in what restaurant they would prefer to eat. In a smart environment using big data, usersâ€™ current activity and past behavior could be incorporated into the suggestion process with an end goal that provides right suggestion at the right time with appropriate location on users personal preferences. The objective of this paper is to provide an overview of contextual suggestion system and a review of TRECâ€™s contextual suggestion track to investigate the approaches have been used in order to develop a model for contextual suggestion.Â Â